2014
DOI: 10.1038/tpj.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants and therapeutic response to antidepressant medication in major depressive disorder

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…36 Additionally, a study investigating the association of CNVs with response to antidepressant medication in major depressive disorder showed no general effect, but the authors noted less response for carriers of CNVs in specific loci, including NRXN1. 37 For therapygenetics, recent studies have mostly used common genetic variants either in selected candidate genes 38 or a hypothesis-free genome-wide approach 39 with no or limited evidence of genetic moderators of treatment response. We used a more refined approach, by investigating rare genic CNVs that are associated with a large risk for ASD as well as other neurodevelopmental and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…36 Additionally, a study investigating the association of CNVs with response to antidepressant medication in major depressive disorder showed no general effect, but the authors noted less response for carriers of CNVs in specific loci, including NRXN1. 37 For therapygenetics, recent studies have mostly used common genetic variants either in selected candidate genes 38 or a hypothesis-free genome-wide approach 39 with no or limited evidence of genetic moderators of treatment response. We used a more refined approach, by investigating rare genic CNVs that are associated with a large risk for ASD as well as other neurodevelopmental and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…While promising, this result underscores one of the challenges in studying TRD: because the cohorts are diffi cult to collect and characterize, there is a paucity of such samples available, so replication has not been possible. (A second study, using the NEWMEDS cohort, also examined copy number variation, but focused on overall antidepressant response rather than treatment resistance [ 36 ]; evidence of enrichment of duplications was not observed. )…”
Section: Association Studies Of Trdmentioning
confidence: 99%
“…They concluded that SVs in drug target genes are important as determinants of individual drug response. Another study conducted in 1,565 patients with MDD revealed association of specific CNVs-including 15q13.3 duplications and exonic neurexin 1 (NRXN1) deletions-with response to serotonergic or noradrenergic antidepressant treatment (Tansey et al 2014). Pharmacogenetic studies targeting CNVs might complement classic pharmacogenetic studies investigating e.g.…”
Section: Future Directions and Clinico-therapeutic Implicationsmentioning
confidence: 99%